Acoustic radiation force impulse tissue characterization of the anterior talofibular ligament: a promising noninvasive approach in ankle imaging - Hotfiel, Thilo; Heiß, Rafael; Janka, Rolf Matthias; Forst, Raimund; Raithel, Martin; Lutter, Christoph; Gelse, Kolja; Pachowsky, Milena; Golditz, Tobias (The physician and sportsmedicine, 2018)
OBJECTIVES: The anterior talofibular ligament (ATFL) is the most frequently injured ligament during inversion strains of the ankle. The purpose of this study was to evaluate the feasibility of acoustic radiation force impulse (ARFI) elastography and to determine the in vivo mechanical properties of the ATFL in healthy athletes. METHODS: Sixty healthy athletes (32 female, 28 male; 28.9 ± 2.1 years) were recruited from the medical and sports faculty. ARFI values, represented as shear wave velocities (SWVs) as well as conventional ultrasound were obtained for the ATFL in neutral ankle position. A clinical assessment was performed in which the American Orthopaedic Foot & Ankle Society (AOFAS) Ankle-Hindfoot Score and the functional ankle ability measure (FAAM) were collected. Interobserver and intraobserver reliability (repeated sessions and repeated days) were assessed using an intra class correlation coefficient (ICC) and typical error (TE) calculation in absolute (TE) and relative units as coefficient of the variation (CV). RESULTS: SWV values of the ATFL had an average velocity of 1.79 ± 0.20 m/s for all participants, with an average of 1.72 ± 0.36 m/s for females and 1.85 ± 0.31 m/s for males. The interobserver and intraobserver reliability revealed an ICC of 0.902 and 0.933 (TE of 0.67 (CV: 5.2%) and 0.52 (CV: 3.84%)), respectively. FAAM and AOFAS revealed the best possible scores. CONCLUSION: ARFI seems to be a valuable diagnostic modality and represents a promising imaging marker for the assessment and monitoring of ankle ligaments in the context of acute and chronic ankle instabilities; ARFI could also be used to investigate loading or sport dependent adaptions.
EVALuna2:36110

Activation of STAT3 integrates common profibrotic pathways to promote fibroblast activation and tissue fibrosis - Chakraborty, Debomita; Sumova, Barbora; Mallano, Tatjana; Chen, Chih-Wei; Distler, Alfiya; Bergmann, Christina; Ludolph, Ingo; Horch, Raymund E.; Gelse, Kolja; Ramming, Andreas; Distler, Oliver; Schett, Georg; et al. (Nature Communications, 2017)
Signal transducer and activator of transcription 3 (STAT3) is phosphorylated by various kinases, several of which have been implicated in aberrant fibroblast activation in fibrotic diseases including systemic sclerosis (SSc). Here we show that profibrotic signals converge on STAT3 and that STAT3 may be an important molecular checkpoint for tissue fibrosis. STAT3 signaling is hyperactivated in SSc in a TGF?-dependent manner. Expression profiling and functional studies in vitro and in vivo demonstrate that STAT3 activation is mediated by the combined action of JAK, SRC, c-ABL, and JNK kinases. STAT3-deficient fibroblasts are less sensitive to the pro-fibrotic effects of TGF?. Fibroblast-specific knockout of STAT3, or its pharmacological inhibition, ameliorate skin fibrosis in experimental mouse models. STAT3 thus integrates several profibrotic signals and might be a core mediator of fibrosis. Considering that several STAT3 inhibitors are currently tested in clinical trials, STAT3 might be a candidate for molecular targeted therapies of SS
EVALuna2:13455

A dual role for UCMA in osteoarthritis-Inhibition of aggrecanases and promotion of bone turnover - Stock, Michael; Menges, Stefanie; Eitzinger, Nicole; Gesslein, Maria; Botschner, Renate; Wormser, Laura; Distler, Alfiya; Schlötzer-Schrehardt, Ursula; Dietel, Katharina; Distler, Jörg; Beyer, Christian; Gelse, Kolja; et al. (Arthritis and Rheumatology, 2017)
Cartilage damage and subchondral bone changes are closely connected in osteoarthritis. How these processes are interlinked is however incompletely understood to date. Here, we investigate the mechanistic role of the cartilage-derived protein UCMA in osteoarthritis-related cartilage and bone changes.UCMA expression was assessed in healthy and osteoarthritic human and mouse cartilage. DMM-induced osteoarthritis was performed in WT and Ucma-deficient mice analysing cartilage and bone changes. UCMA-collagen interactions, effect of UCMA on aggrecanase activity and the impact of recombinant UCMA on osteoclast differentiation were studied in vitro.UCMA was found overexpressed in human and mouse osteoarthritic cartilage. DMM-triggered cartilage changes were aggravated in Ucma-deficient mice compared to WT littermates, showing increased structural damage, proteoglycan loss and chondrocyte cell death indicating chondroprotective effects of UCMA. Moreover, UCMA inhibited ADAMTS-dependent aggrecanase activity and directly interacted with cartilage-specific collagen types. In contrast, osteoarthritis-related bone changes were significantly reduced in Ucma-deficient mice, showing less pronounced osteophyte formation and subchondral bone sclerosis. Mechanistically, UCMA directly promoted osteoclast differentiation in vitro.UCMA links cartilage with bone changes in osteoarthritis, supporting cartilage integrity as an endogenous inhibitor of aggrecanases on the one hand, and promoting osteoclastogenesis and subchondral bone turnover on the other hand. Hence, UCMA represents an important link between cartilage and bone in osteoarthritis. This article is protected by copyright. All rights reserved.
EVALuna2:10230

Aktuelle Therapiekonzepte bei Acetabulumfrakturen - Gelse, Kolja (Chirurgische Praxis, 2019)
Fractures of the acetabulum occur in a bimodal distribution. In young patients, fractures of the acetabulum are predominantly induced by high-energy trauma, whereas in the elderly population, even minor trauma can lead to fractures of the acetabulum due to osteoporotic bone. The exact classification of the fracture is important for the assessment of the stability, and thus for the decision for conservative or operative therapy. While fractures of the posterior column and posterior wall are treated by the dorsal approach, there is a trend towards the use of the intrapelvic and pararectus approach for most other fracture types. Basically, the restoration of the joint surface is of major importance to avoid the incidence of posttraumatic osteoarthritis, while tissue trophic and vascularization must not be affected. In certain cases, minimally invasive approaches may be reasonable to prepare secondary arthroplasty. Primary arthroplasty may be performed in those cases with defects that cannot be restored anymore, severe osteoporosis or addititve fractures of the proximal femur. It may be necessary to apply additive osteosynthetic stabilisation. For younger patients, anatomic reconstruction is of major importance, whereas in geriatric patients, the demand for early mobilisation plays a crucial role regarding the decision of the therapeutic strategy.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Acetabulum fracture; Biomechanics; Classification; Internal fixation; Surgical approach

Assessing Foot Loads in Continuous Passive Motion (CPM) and Active Knee Joint Motion Devices - Stolz, Benedikt; Grim, Casper; Lutter, Christoph; Gelse, Kolja; Schell, Monika; Swoboda, Bernd; Carl, Hans-Dieter; Hotfiel, Thilo (Sportverletzung-Sportschaden, 2019)
BACKGROUND: Continuous passive motion (CPM) and active knee joint motion devices are commonly applied after various surgical procedures. Despite the growing use of active motion devices, there is a paucity of data comparing plantar loads between the different mobilization techniques. The aim of this study was to investigate foot loads during knee joint mobilization in continuous passive and active knee joint motion devices and to compare this data to the physiological load of full weight-bearing. PATIENTS/MATERIAL AND METHODS: Fifteen healthy participants (7 women and 8 men, 25 ± 3 years, 66 ± 6 kg, 175 ± 10 cm, BMI 21.9 ± 2) were recruited. Plantar loads were measured via dynamic pedobarography using a continuous passive motion device (ARTROMOT-K1, ORMED GmbH, Freiburg, Germany) and an active motion device (CAMOped, OPED AG, Cham, Switzerland), each with a restricted range of motion of 0-0-90° (ex/flex) and free ROM for the knee joint. For the active motion device, cycles were performed at four different resistance levels (0-III). Data were assessed using the pedar® X system (Novel Inc., Munich, Germany), which monitors loads from the foot-sole interface. Force values were compared between motion devices and normal gait, which served as the reference for conditions of full weight-bearing. P-values of < 0.05 were considered statistically signiﬁcant. RESULTS: Normal gait revealed peak forces of 694 ± 96 N, defined as 100 %. The CPM device produced plantar forces of less than 1.5 N. Using the active motion device in the setting of 0-0-90° produced foot loads of < 1.5 N (resistance 0-II) and 3.4 ± 9.3 N with a resistance of III (p < 0.001). Conditions of free ROM resulted in foot loads of 4.5 ± 4.5 N (resistance 0), 7.7 ± 10.7 N (resistance I), 6.7 ± 10.4 (resistance II) and 6.7 ± 6.9 N with a resistance of III (p < 0.001), corresponding to 0.6 %, 1.1 %, 1.0 % and 1.0 % of full weight-bearing, respectively. CONCLUSION: Motion exercises of the knee joint can be performed both with passive and active devices in accordance with strict weight-bearing restrictions, which are often recommended by surgeons. Also, active motion devices can be used when the ankle joint or foot have to be offloaded. Further studies assessing intraarticular joint load conditions have to be performed to confirm the findings obtained in this study.
EVALuna2:205192

Autologous chondrocyte implantation (ACI) for cartilage defects of the knee: A guideline by the working group "Clinical Tissue Regeneration" of the German Society of Orthopaedics and Trauma (DGOU) - Niemeyer, P.; Albrecht, D.; Andereya, S.; Angele, P.; Ateschrang, A.; Aurich, M.; Baumann, M.; Bosch, U.; Erggelet, C.; Fickert, S.; Gebhard, H.; Gelse, Kolja; et al. (Knee, 2016)
Autologous chondrocyte implantation (ACI) is an established and well-accepted procedure for the treatment of localised full-thickness cartilage defects of the knee.The present review of the working group "Clinical Tissue Regeneration" of the German Society of Orthopaedics and Trauma (DGOU) describes the biology and function of healthy articular cartilage, the present state of knowledge concerning therapeutic consequences of primary cartilage lesions and the suitable indication for ACI.Based on best available scientific evidence, an indication for ACI is given for symptomatic cartilage defects starting from defect sizes of more than three to four square centimetres; in the case of young and active sports patients at 2.5cm(2), while advanced degenerative joint disease needs to be considered as the most important contraindication.The present review gives a concise overview on important scientific background and the results of clinical studies and discusses the advantages and disadvantages of ACI.Non-systematic Review.
EVALuna2:15841

Autologous Conditioned Plasma Versus Placebo Injection Therapy in Lateral Epicondylitis of the Elbow: A Double Blind, Randomized Study - Willauschus, Wolfgang; Sauer, Felix; Kuepper, Thomas; Schoeffl, Isabelle; Lutter, Christoph; Gelse, Kolja; Dickschas, Joerg; Schöffl, Volker (Sportverletzung-Sportschaden, 2017)
Introduction There are various therapeutic approaches to the treatment of lateral epicondylitis, a highly prevalent musculoskeletal disorder. Recently, injection therapy with autologous conditioned plasma (ACP) has shown promise as a new approach. Methods Set up as a prospective, double-blind, randomized controlled clinical trial, this study involved 50 patients with lateral epicondylitis. Following external randomization, 25 patients received one round of injection therapy with ACP (platelet rich plasma, PRP), while the remaining 25 patients received a placebo of 0.9 % NaCl. All patients were re-evaluated with respect to lateral epicondylitis of the elbow at four-weeks and six-months post-injection. Results Out of 50 patients, 36 qualified for reevaluation, 18 patients from the ACP therapy group and 18 from the placebo group. The initial Disability of the Arm, Shoulder and Hand (DASH) score for all reevaluated patients was 36.4 in the ACP group, and 41.0 in the placebo group; both groups exhibited decreased DASH scores at the four-week and six-month post-injection follow-up (6 months: ACP 30.1, placebo 25.8). The decrease of the DASH score after 4 weeks was greater and qualified as statistically significant in the placebo group (p = 0.041), compared to the DASH score decrease in the ACP treatment group, which was statistically non-significant. Additionally, the difference between the DASH scores of the treatment and placebo groups was statistically non-significant four weeks and six months after treatment. Discussion The results of this study suggest a therapeutic effect in both the ACP and placebo groups, with no evidence for a therapeutically significant difference between ACP and placebo treatments. It is hypothesized that, in accordance with the study protocols, injection with a local anaesthetic prior to ACP therapy may have an influence on the therapeutic effect of ACP. Future studies have to confirm recent findings that demonstrated a minimizing, or even inhibiting, action of local anaesthetics on the effects of ACP/PRP. Conclusion The effect of ACP/PRP injections needs to be investigated in future studies under standardized conditions.
EVALuna2:15867

Cementless femoral components in bicondylar hybrid knee arthroplasty in patients with rheumatoid arthritis: A 10-year survivorship analysis - Hotfiel, Thilo; Carl, Hans-Dieter; Eibenberger, Teresa; Gelse, Kolja; Weiss, Julian; Jendrissek, Andreas; Swoboda, Bernd (Journal of Orthopaedic Surgery, 2017)
Total knee arthroplasty (TKA) has been established as a successful surgical treatment in the late stages of rheumatoid joint destruction. The purpose of this study was to review the clinical outcome and survivorship in rheumatoid arthritis (RA) patients undergoing TKA in hybrid technique with a cementless fixation of the femoral component.We analysed retrospectively 66 RA patients who underwent 72 TKAs (P.F.C. Sigma®). Mean follow-up time was 124 ± 41 months. To evaluate postoperative clinical outcome, knee injury and osteoarthritis outcome score (KOOS) and Oxford knee score (OKS) were assessed. Kaplan-Meier analysis was used to calculate survivorship. The primary outcome was revision for any reason.Thirty-four patients (36 knees) died and two patients (2 knees) were lost to follow-up. Three patients (four knees) did not agree to participate. Twenty-seven patients (30 knees) were available for assessing clinical scores. The average scores were 85 ± 14 for KOOS and 34 ± 10 for OKS. In three patients (three knees), revision was necessary, including restricted range of motion ( n = 1), instability ( n = 1), and infection ( n = 1). There were no cases of loosening in this cohort study. The survival rates were 100% at 5 years, 97.1% at 10 years (95% CI 89.0-99.2%) and 95.6% at 15 years (95% CI 86.9-98.5%).This study confirms that excellent clinical results and a good 10-year survivorship can be obtained with hybrid fixation technique in TKA in the unique population of RA patients.
EVALuna2:10912

Composition of TWIST1 dimers regulates fibroblast activation and tissue fibrosis - Palumbo-Zerr, Katrin; Soare, Alina; Zerr, Pawel; Liebl, Andrea; Mancuso, Rossella; Tomcik, Michal; Sumova, Barbora; Dees, Clara; Chen, Chih-Wei; Wohlfahrt, Thomas; Mallano, Tatjana; Distler, Alfiya; et al. (Annals of the Rheumatic Diseases, 2017)
TWIST1 is a member of the class B of basic helix-loop-helix transcription factors that regulates cell lineage determination and differentiation and has been implicated in epithelial-to-mesenchymal transition. Here, we aimed to investigate the role of TWIST1 for the activation of resident fibroblasts in systemic sclerosis (SSc).The expression of Twist1 in fibroblasts was modulated by forced overexpression or siRNA-mediated knockdown. Interaction of Twist1, E12 and inhibitor Of differentiation (Id) was analysed by co-immunoprecipitation. The role of Twist1 in vivo was evaluated using inducible, conditional knockout mice with either ubiquitous or fibroblast-specific depletion of Twist1. Mice were either challenged with bleomycin or overexpressing a constitutively active transforming growth factor (TGF)? receptor I.The expression of TWIST1 was increased in fibroblasts in fibrotic human and murine skin in a TGF?/SMAD3-dependent manner. TWIST1 in turn enhanced TGF?-induced fibroblast activation in a p38-dependent manner. The stimulatory effects of TWIST1 on resident fibroblasts were mediated by TWIST1 homodimers. TGF? promotes the formation of TWIST1 homodimers by upregulation of TWIST1 and by induction of inhibitor of DNA-binding proteins, which have high affinity for E12/E47 and compete against TWIST1 for E12/E47 binding. Mice with selective depletion of Twist1 in fibroblasts are protected from experimental skin fibrosis in different murine models to a comparable degree as mice with ubiquitous depletion of Twist1.Our data identify TWIST1 as a central pro-fibrotic factor in SSc, which facilitates fibroblast activation by amplifying TGF? signalling. Targeting of TWIST1 may thus be a novel approach to normalise aberrant TGF? signalling in SSc.
EVALuna2:13273

Contrast-Enhanced Ultrasound as a New Investigative Tool in Diagnostic Imaging of Muscle Injuries-A Pilot Study Evaluating Conventional Ultrasound, CEUS, and Findings in MRI - Hotfiel, Thilo; Heiss, Rafael; Swoboda, Bernd; Kellermann, Marion; Gelse, Kolja; Grim, Casper; Strobel, Deike; Wildner, Dane (Clinical Journal of Sport Medicine, 2017)
To emphasize the diagnostic value of contrast-enhanced ultrasound (CEUS) in the imaging of muscle injuries with different degrees of severity by comparing findings to established imaging modalities such as conventional ultrasound and magnetic resonance imaging (MRI).Case series.Institutional study. Conventional ultrasound and CEUS were performed in the Department of Internal Medicine. Magnetic resonance imaging was carried out in the Department of Radiology within the Magnetom Avanto 1.5T and Magnetom Skyra fit 3T (Siemens Healthineers, Erlangen, Germany) and in the Institution of Imaging Diagnostics and Therapy (Magnetom Avanto 1.5T; Siemens, Erlangen, Germany).Fifteen patients who underwent an acute muscle injury were recruited.The appearance and detectable size of muscle injuries were compared between each imaging modality. The injuries were assessed by 3 independent observers and blinded between imaging modalities.All 15 injuries were identified on MRI and CEUS, whereas 10 injuries showed abnormalities in conventional ultrasound. The determination and measurement revealed significant differences between conventional ultrasound and CEUS depending on injury severity. Contrast-enhanced ultrasound revealed an impairment of microcirculation in grade I lesions (corresponding to intramuscular edema observed in MRI), which was not detectable using conventional ultrasound.Our results indicate that performing CEUS seems to be a sensitive additional diagnostic modality in the early assessment of muscle injuries. Our results highlight the advantages of CEUS in the imaging of low-grade lesions when compared with conventional ultrasound, as this was the more accurate modality for identifying intramuscular edema.
EVALuna:34225

Correction: Significance of Matrix-augmented Bone Marrow Stimulation for Treatment of Cartilage Defects of the Knee: A Consensus Statement of the DGOU Working Group on Tissue Regeneration - Niemeyer, Philipp; Becher, Christoph; Brucker, Peter U; Buhs, Matthias; Fickert, Stefan; Gelse, Kolja; Günther, Daniel; Kaelin, Raphael; Kreuz, Peter; Lützner, Jörg; Nehrer, Stefan; Madry, Henning; et al. (Zeitschrift für Orthopädie und Unfallchirurgie, 2018)
EVALuna2:104971

Degenerative Cartilage Lesions of the Medial Knee Compartment. Associated Factors, Operative Options, and Preliminary Results from the Cartilage Registry DGOU - Lungwitz, Suzanne; Niemeyer, Philipp; Maurer, Julia; Fritz, Jürgen; Albrecht, D.; Angele, Peter; Fickert, Stefan; Gelse, Kolja; Zinser, Wolfgang; Hofmann, Gunther O.; Spahn, Gunter (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
Purpose This study was aimed to determine the impact of bioregenerative operations in case of degenerative cartilage lesions within the media knee compartment. Material and Methods The CartilageRegistry DGOU was founded in 2013. At the deadline August 2016 a total of 1847 patients were included. A total of 23.3% (n = 432) was suffering from a degenerative cartilage lesion in the medial compartment. Follow-up was performed after 6, 12, and 24 months (online evaluation). The patients were asked for their subject feeling as well as the KOOS (Knee injury and Osteoarthritis Outcome Score) was determined. Results Most of the patients (n = 358) suffered from a single femoral lesion. In 25 cases single tibial and in 49 cases combined defects (kissing lesions) were addressed by different treatment options: 39.9% autologous chondrocyte transplantation, in 8.1% in combination with a spongiosa plasty. Other treatments were drilling, microfracturing with or without matrix. In 17.9% the surgeons had chosen combined methods. The bioregenerative treatment was combined with a concomitant operation in 39.7% in patients with medial, in 56.0% in patients with a tibial, and in 67.9% in patients with combined defects. The mostly performed additional operations were osteotomies. There were no gender differences at baseline or during follow-up. The history of patients with femoral defects was shorter than in the other groups. The patients with medial defects judged the subjective outcome significant more frequently better after 6, 12, or 24 months compared with the other groups. The KOOS raised from baseline (median 52 points) to a median of 75 after 6, to 78 points after 12, and to 80 points after 24 months. Patients with femoral defects had a better KOOS-outcome in tendency. Revision operations were required in 7.1%. Conclusions The treatment of degenerative cartilage lesions (respective early OA) by bioregenerative procedures are well-established measures. These treatments are sufficient to produce high patients satisfaction and acceptable short/midterm results.
CRIS-Team Scopus Importer:2019-10-25
Keywords: cartilage; CartilageRegistry; degeneration; early-OA; knee

Evaluation of surfactant proteins A, B, C, and D in articular cartilage, synovial membrane and synovial fluid of healthy as well as patients with osteoarthritis and rheumatoid arthritis - Hartjen, Nadine; Bräuer, Lars; Reiss, Beate; Claassen, Horst; Beileke, Stephanie; Garreis, Fabian; Hoogeboom, Sebastian; Tsokos, Michael; Etzold, Saskia; Mueller-Hilke, Brigitte; Gelse, Kolja; Mueller, Thomas; et al. (PLoS ONE, 2018)
OBJECTIVE: Surfactant Proteins (SPs) are well known from lung and form, along with phospholipids, a surface-active-layer at the liquid-air-interface of the alveolar lining. They play a major protective role by lowering surface tension, activating innate and adaptive immune defense at the lung mucosal interface, especially during infection. We analyzed the regulation of SPs in human and mouse articular chondrocytes, synoviocytes, and synovial fluid under healthy and inflammatory conditions, as well as in tissues of patients suffering from osteoarthritis and rheumatoid arthritis. METHODS: Immunohistochemistry, RT-PCR, qRT-PCR, ELISA, Western blotting were performed in cell cultures and tissue samples to determine localization, regulation, and concentration of SPs. RESULTS: All four SPs, were expressed by healthy human and mouse articular chondrocytes and synoviocytes and were also present in synovial fluid. Treatment with inflammatory mediators like IL-1β and TNF-α led to short-term upregulation of individual SPs in vitro. In tissues from patients with osteoarthritis and rheumatoid arthritis, protein levels of all four SPs increased significantly compared to the controls used. CONCLUSION: These results show the distribution and amount of SPs in tissues of articular joints. They are produced by chondrocytes and synoviocytes and occur in measurable amounts in synovial fluid. All four SPs seem to be differently regulated under pathologic conditions. Their physiological functions in lowering surface tension and immune defense need further elucidation and make them potential candidates for therapeutic intervention.
EVALuna2:35305

Functional ankle instability as a risk factor for osteoarthritis: Using T2-mapping to analyze early cartilage degeneration in the ankle joint of young athletes - Golditz, Tobias; Steib, Simon; Pfeifer, Klaus; Uder, Michael; Gelse, Kolja; Janka, Rolf Matthias; Hennig, Friedrich; Welsch, Götz (Osteoarthritis and Cartilage, 2014)
Objective: The aim of this study was to investigate, using T2-mapping, the impact of functional instability in the ankle joint on the development of early cartilage damage. Methods: Ethical approval for this study was provided. Thirty-six volunteers from the university sports program were divided into three groups according to their ankle status: functional ankle instability (FAI, initial ankle sprain with residual instability); ankle sprain Copers (initial sprain, without residual instability); and controls (without a history of ankle injuries). Quantitative T2-mapping magnetic resonance imaging (MRI) was performed at the beginning ('early-unloading') and at the end ('late-unloading') of the MR-examination, with a mean time span of 27min. Zonal region-of-interest T2-mapping was performed on the talar and tibial cartilage in the deep and superficial layers. The inter-group comparisons of T2-values were analyzed using paired and unpaired t-tests. Statistical analysis of variance was performed. Results: T2-values showed significant to highly significant differences in 11 of 12 regions throughout the groups. In early-unloading, the FAI-group showed a significant increase in quantitative T2-values in the medial, talar regions (. P=0.008, P=0.027), whereas the Coper-group showed this enhancement in the central-lateral regions (. P=0.05). Especially the comparison of early-loading to late-unloading values revealed significantly decreasing T2-values over time laterally and significantly increasing T2-values medially in the FAI-group, which were not present in the Coper- or control-group. Conclusion: Functional instability causes unbalanced loading in the ankle joint, resulting in cartilage alterations as assessed by quantitative T2-mapping. This approach can visualize and localize early cartilage abnormalities, possibly enabling specific treatment options to prevent osteoarthritis in young athletes.
UnivIS-Import:2015-03-09:Pub.2014.phil.dps.iss.psbg.functi
Keywords: Functional ankle instability; Magnetic resonance imaging; Osteoarthritis; Sports medicine; T2-mapping

gagCEST imaging at 3 T MRI in patients with articular cartilage lesions of the knee and intraoperative validation - Söllner, Stefan; Welsch, G. H.; Gelse, Kolja; Goldmann, A.; Kleyer, Arnd; Schett, Georg; Pachowsky, Milena (Osteoarthritis and Cartilage, 2021)
Objective: The aim of this study was to compare glycosaminoglycan chemical exchange saturation transfer (gagCEST) of knee cartilage with intraoperative results for the assessment of early osteoarthritis (OA) and to define gagCEST values for the differentiation between healthy and degenerated cartilage. Design: Twenty-one patients with cartilage lesions or moderate OA were examined using 3 T Magnetic Resonance Imaging (MRI). In this prospective study, regions of interest (ROIs) were examined by a sagittal gagCEST analysis and a morphological high-resolution three-dimensional, fat-saturated proton-density space sequence. Cartilage lesions were identified arthroscopically, graded by the International Cartilage Repair Society (ICRS) score in 42 defined ROIs per patient and consecutively compared with mean gagCEST values using analysis of variance and Spearman's rank correlation test. Receiver operating characteristics (ROC) curves were applied to identify gagCEST threshold values to differentiate between the ICRS grades. Results: A total of 882 ROIs were examined and graduated in ICRS score 0 (67.3%), 1 (25.2%), 2 (6.2%) and the merged ICRS 3 and 4 (1.0%). gagCEST values decreased with increasing grade of cartilage damage with a negative correlation between gagCEST values and ICRS scores. A gagCEST value threshold of 3.55% was identified to differentiate between ICRS score 0 (normal) and all other grades. Conclusions: gagCEST reflects the content of glycosaminoglycan and might provide a diagnostic tool for the detection of early knee-joint cartilage damage and for the non-invasive subtle differentiation between ICRS grades by MRI even at early stages in clinical practice.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Cartilage; Chemical exchange saturation transfer; MRI; Osteoarthritis

High-Energy X-Ray Talbot-Lau Radiography of a Human Knee - Horn, Florian; Gelse, Kolja; Jabari, Samir; Hauke, Christian; Käppler, Sebastian; Ludwig, Veronika; Meyer, Pascal; Michel, Thilo; Mohr, Jürgen; Pelzer, Georg; Rieger, Jens; Riess, Christian; et al. (Physics in Medicine and Biology, 2017)
Keywords: dark-field; high-energy; chondrocalcinosis; x-ray imaging; phase-contrast; TalbotLau imaging

Human synovia contains trefoil factor family (TFF) peptides 1-3 although synovial membrane only produces TFF3: Implications in osteoarthritis and rheumatoid arthritis - Popp, Judith; Schicht, Martin; Garreis, Fabian; Klinger, Patricia; Gelse, Kolja; Sesselmann, Stefan; Tsokos, Michael; Etzold, Saskia; Stiller, Dankwart; Claassen, Horst; Paulsen, Friedrich (International Journal of Molecular Sciences, 2019)
Objective: Trefoil factor family peptide 3 (TFF3) has been shown to support catabolic functions in cases of osteoarthritis (OA). As in joint physiology and diseases such as OA, the synovial membrane (SM) of the joint capsule also plays a central role. We analyze the ability of SM to produce TFF compare healthy SM and its secretion product synovial fluid (SF) with SM and SF from patients suffering from OA or rheumatoid arthritis (RA). Methods: Real-time PCR and ELISA were used to measure the expression of TFFs in healthy SM and SM from patients suffering from OA or RA. For tissue localization, we investigated TFF1-3 in differently aged human SM of healthy donors by means of immunohistochemistry, real-time PCR and Western blot. Results: Only TFF3 but not TFF1 and -2 was expressed in SM from healthy donors as well as cases of OA or RA on protein and mRNA level. In contrast, all three TFFs were detected in all samples of SF on the protein level. No significant changes were observed for TFF1 at all. TFF2 was significantly upregulated in RA samples in comparison to OA samples. TFF3 protein was significantly downregulated in OA samples in comparison to healthy samples and cases of RA significantly upregulated compared to OA. In contrast, in SM TFF3 protein was not significantly regulated. Conclusion: The data demonstrate the production of TFF3 in SM. Unexpectedly, SF contains all three known TFF peptides. As neither articular cartilage nor SM produce TFF1 and TFF2, we speculate that these originate with high probability from blood serum.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Osteoarthritis (OA); Rheumatoid arthritis (RA); Synovial fluid (SF); Synovial membrane (SM); Trefoil factor family peptides (TFF)

Inhibition of Notch1 promotes hedgehog signalling in a HES1-dependent manner in chondrocytes and exacerbates experimental osteoarthritis - Lin, Neng-Yu; Distler, Alfiya; Beyer, Christian; Philipi-Schöbinger, Ariella; Breda, Silvia; Dees, Clara; Stock, Michael; Tomcik, Michal; Niemeier, Andreas; Dell'Accio, Francesco; Gelse, Kolja; Mattson, Mark P; et al. (Annals of the Rheumatic Diseases, 2016)
Notch ligands and receptors have recently been shown to be differentially expressed in osteoarthritis (OA). We aim to further elucidate the functional role of Notch signalling in OA using Notch1 antisense transgenic (Notch1 AS) mice.Notch and hedgehog signalling were analysed by real-time PCR and immunohistochemistry. Notch-1 AS mice were employed as a model of impaired Notch signalling in vivo. Experimental OA was induced by destabilisation of the medial meniscus (DMM). The extent of cartilage destruction and osteophyte formation was analysed by safranin-O staining with subsequent assessment of the Osteoarthritis Research Society International (OARSI) and Mankin scores and µCT scanning. Collagen X staining was used as a marker of chondrocyte hypertrophy. The role of hairy/enhancer of split 1 (Hes-1) was investigated with knockdown and overexpression experiments.Notch signalling was activated in human and murine OA with increased expression of Jagged1, Notch-1, accumulation of the Notch intracellular domain 1 and increased transcription of Hes-1. Notch1 AS mice showed exacerbated OA with increases in OARSI scores, osteophyte formation, increased subchondral bone plate density, collagen X and osteocalcin expression and elevated levels of Epas1 and ADAM-TS5 mRNA. Inhibition of the Notch pathway induced activation of hedgehog signalling with induction of Gli-1 and Gli-2 and increased transcription of hedgehog target genes. The regulatory effects of Notch signalling on Gli-expression were mimicked by Hes-1.Inhibition of Notch signalling activates hedgehog signalling, enhances chondrocyte hypertrophy and exacerbates experimental OA including osteophyte formation. These data suggest that the activation of the Notch pathway may limit aberrant hedgehog signalling in OA.
EVALuna2:13184

Inhibition of sumoylation prevents experimental fibrosis - Khodzhigorova, Aisa; Distler, Alfiya; Lang, Veronika; Dees, Clara; Schneider, Holm; Beyer, Christian; Gelse, Kolja; Distler, Oliver; Schett, Georg; Distler, Jörg (Annals of the Rheumatic Diseases, 2012)
Objectives: Fibrosis is a predominant cause of death in systemic sclerosis (SSc). First epigenetic modifications have recently been shown to contribute to activation of SSc fibroblasts. Here, we investigated inhibition of sumoylation as a novel antifibrotic approach. Methods: Sumoylation was inhibited by siRNA-mediated knockdown of the Small Ubiquitin-like MOdifiers (SUMO) E2-conjugating enzyme Ubc9, which is essential for sumoylation. The effects of knockdown of Ubc9 were analysed in bleomycin-induced dermal fibrosis, and in the model of fibrosis induced by overexpression of a constitutively active TGF-beta receptor type I (TBR). SUMO-1 and phosphorylated Smad3 were detected by immunohistochemistry. Results: Increased staining for SUMO-1 was detected in patients with SSc and in experimental fibrosis. Inhibition of sumoylation exerted potent antifibrotic effects and prevented dermal thickening, myofibroblast differentiation and accumulation of collagen induced by bleomycin, or by overexpression of constitutively active TBR. Moreover, knockdown of Ubc9 reduced the accumulation of phosphorylated Smad3 in experimental fibrosis indicating that inhibition of sumoylation may normalise canonical TGF-β signalling in vivo. Conclusions: We demonstrate that inhibition of sumoylation reduces canonical TGF-β signalling and prevents experimental fibrosis in different preclinical models. These data provide first evidence that targeting of aberrant sumoylation may be a novel therapeutic approach for fibrotic diseases.
CRIS-Team Scopus Importer:2020-07-01

Intramuscular Perfusion Response in Delayed Onset Muscle Soreness (DOMS): A Quantitative Analysis with Contrast-Enhanced Ultrasound (CEUS) - Kellermann, Marion; Heiss, Rafael; Swoboda, Bernd; Gelse, Kolja; Freiwald, Jürgen; Grim, Casper; Nagel, Armin Michael; Uder, Michael; Wildner, Dane; Hotfiel, Thilo (International Journal of Sports Medicine, 2017)
The purpose of this study was to analyse intramuscular perfusion response in ultrastructural muscle lesions, by applying contrast-enhanced ultrasound (CEUS) to a delayed onset muscle soreness (DOMS) model. Results of this analysis were compared to high-resolution 3 Tesla MRI T2-weighted sequences. 14 healthy participants were recruited. Average perfusion parameters, represented as Peak enhancement (contrast agent inflow) and wash-in area under curve (WiAUC) of the gastrocnemius (GM) and soleus muscle (SM) were assessed before (baseline) and 60 h after inducing DOMS by eccentric exercise. Additionally, conventional ultrasound, high-resolution 3T MRI, creatine kinase level, range of motion (ROM) of the ankle joint, calf circumference and muscle soreness data were collected. Perfusion quantification revealed a statistically significant increase of intramuscular perfusion, corresponding to an increase in peak enhancement of 129.6% (p=0.0031) and in WiAUC of 115.2% (p=0.0107) in the gastrocnemius muscle at post-intervention. At follow-up, the MRI investigations showed intramuscular oedema for GM in all participants corresponding to a significant rise in T2 signal intensity (p=0.001) and in T2 time value (p=0.005). CEUS seems to be able to detect intramuscular perfusion changes and therefore may contribute to gaining deeper insight into the histopathology, inflammatory reactions and regeneration processes of ultrastructural muscle lesions.
EVALuna2:10913

In vivo evaluation of gene transfer into mesenchymal cells (in view of cartilage repair). - Gelse, Kolja; Schneider, Holm (Methods in Molecular Biology, 2011)
Gene transfer of specific growth factors is suitable for inducing chondrogenic differentiation of -mesenchymal cells to be used for cartilage regeneration. However, extent and quality of repair tissue formation also depend on biomechanical and metabolic influences that can only be studied in vivo. We describe three methods to evaluate viral gene transfer into mesenchymal cells in animal models of articular cartilage defects, e.g., mouse, rat and miniature pig models, focussing on the repair of hyaline cartilage tissue.
CRIS-Team Scopus Importer:2020-07-01

JAK1-dependent transphosphorylation of JAK2 limits the antifibrotic effects of selective JAK2 inhibitors on long-term treatment - Zhang, Yun; Liang, Ruifang; Chen, Chih-Wei; Mallano, Tatjana; Dees, Clara; Distler, Alfiya; Reich, Adam; Bergmann, Christina; Ramming, Andreas; Gelse, Kolja; Mielenz, Dirk; Distler, Oliver; et al. (Annals of the Rheumatic Diseases, 2017)
Janus kinase 2 (JAK2) has recently been described as a novel downstream mediator of the pro-fibrotic effects of transforming growth factor-?. Although JAK2 inhibitors are in clinical use for myelodysplastic syndromes, patients often rapidly develop resistance. Tumour cells can escape the therapeutic effects of selective JAK2 inhibitors by mutation-independent transactivation of JAK2 by JAK1. Here, we used selective JAK2 inhibition as a model to test the hypothesis that chronic treatment may provoke resistance by facilitating non-physiological signalling pathways in fibroblasts.The antifibrotic effects of long-term treatment with selective JAK2 inhibitors and reactivation of JAK2 signalling by JAK1-dependent transphosphorylation was analysed in cultured fibroblasts and experimental dermal and pulmonary fibrosis. Combined JAK1/JAK2 inhibition and co-treatment with an HSP90 inhibitor were evaluated as strategies to overcome resistance.The antifibrotic effects of selective JAK2 inhibitors on fibroblasts decreased with prolonged treatment as JAK2 signalling was reactivated by JAK1-dependent transphosphorylation of JAK2. This reactivation could be prevented by HSP90 inhibition, which destabilised JAK2 protein, or with combined JAK1/JAK2 inhibitors. Treatment with combined JAK1/JAK2 inhibitors or with JAK2 inhibitors in combination with HSP90 inhibitors was more effective than monotherapy with JAK2 inhibitors in bleomycin-induced pulmonary fibrosis and in adTBR-induced dermal fibrosis.Fibroblasts can develop resistance to chronic treatment with JAK2 inhibitors by induction of non-physiological JAK1-dependent transactivation of JAK2 and that inhibition of this compensatory signalling pathway, for example, by co-inhibition of JAK1 or HSP90 is important to maintain the antifibrotic effects of JAK2 inhibition with long-term treatment.
EVALuna2:13270

Lenalidomide enhances MOR202-dependent macrophage-mediated effector functions via the vitamin D pathway - Busch, Leonhard; Mougiakakos, Dimitrios; Büttner-Herold, Maike; Müller, Miriam J.; Volmer, Dietrich A.; Bach, Christian; Fabri, Mario; Bittenbring, Jörg T.; Neumann, Frank; Boxhammer, Rainer; Nolting, Jens; Bisht, Savita; et al. (Leukemia, 2018)
Macrophages are key mediators of the therapeutic effects exerted by monoclonal antibodies, such as the anti-CD38 antibody MOR202, currently introduced in multiple myeloma (MM) therapy. Therefore, it is important to understand how antibody-mediated effector functions of myeloma-associated macrophages (MAMs) are regulated. Here, we focused on the effects of vitamin D, a known regulator of macrophage effector functions. Consequently, it was the aim of this study to assess whether modulation of the vitamin D pathway alters the tumoricidal activity of MAMs. Here, we demonstrate that MAMs display a defective vitamin D pathway with reduced expression level of CYP27B1 and limited tumoricidal activity which can be restored by the IMiD lenalidomide in vitro. Furthermore, our data indicate that the vitamin D pathway of MAMs from MM patients does recover during an IMiD-containing therapy shown by an improved MOR202-mediated cytotoxic activity of these MAMs against primary MM cells ex vivo. Here, the ex vivo cytotoxic activity could be further enhanced by vitamin D supplementation. These data suggest that vitamin D holds a key role for the effector functions of MAMs and that vitamin D supplementation in IMiD combination trials could further increase the therapeutic efficacy of anti-CD38 antibodies such as MOR202, which remains to be investigated in clinical studies.
EVALuna2:34165

Limited evidence of chondrocyte outgrowth from adult human articular cartilage - Zingler, Christian; Carl, Hans-Dieter; Swoboda, Bernd; Krinner, S.; Hennig, Friedrich; Gelse, Kolja (Osteoarthritis and Cartilage, 2016)
Cellular outgrowth from articular cartilage tissue has been described in a number of recent experimental studies. The aim of this study was to investigate the occurrence of cellular outgrowth from articular cartilage explants isolated from adult human donors.Macroscopically intact articular cartilage specimens were isolated from adult human donors and cultured either in their native status, or in a cleansed status achieved by forced washing to minimize attaching cells. Additionally, the effect of chemotactic stimuli including cell lysate, High-Mobility-Group-Protein B1 (HMGB-1), Trefoil-factor 3 (TFF3), bone morphogenetic protein-2 (BMP-2), transforming growth factor-ß1 (TGF-ß1), or three-dimensional fibrin or collagen matrices were investigated. Co-cultures with synovial membrane served as a positive control for a source of migratory cells. The occurrence of cellular outgrowth was analyzed by histological examination after a culture period of 4 weeks.Spontaneous cellular outgrowth from cleansed cartilage specimens was not observed at a relevant level and could not significantly be induced by chemotactic stimuli or three-dimensional matrices either. A forming cartilage-adjoining cell layer was only apparent in the case of native cartilage explants with cellular remnants from surgical isolation or in co-culture experiments with synovial membrane.The relevance of cellular outgrowth from cartilage tissue is largely absent in the case of adult human articular cartilage samples. A cartilage-adjoining cell layer forming around the explants may instead originate from still attaching cells that remained from surgical isolation.
EVALuna2:10905

Limited integrative repair capacity of native cartilage autografts within cartilage defects in a sheep model - Gelse, Kolja; Riedel, Dominic; Pachowsky, Milena; Hennig, Friedrich; Trattnig, Siegfried; Welsch, Götz (Journal of Orthopaedic Research, 2015)
The purpose of this study was to investigate integration and cellular outgrowth of native cartilage autografts transplanted into articular cartilage defects. Native cartilage autografts were applied into chondral defects in the femoral condyle of adult sheep. Within the defects, the calcified cartilage layer was either left intact or perforated to induce bone marrow stimulation. Empty defects served as controls. The joints were analyzed after 6 and 26 weeks by macroscopic and histological analysis using the ICRS II Score and Modified O'Driscoll Scores. Non-treated defects did not show any endogenous regenerative response and bone marrow stimulation induced fibrous repair tissue. Transplanted native cartilage grafts only insufficiently integrated with the defect borders. Cell death and loss of proteoglycans were present at the margins of the grafts at 6 weeks, which was only partially restored at 26 weeks. Significant cellular outgrowth from the grafts or defect borders could not be observed. Bonding of the grafts could be improved by additional bone marrow stimulation providing ingrowing cells that formed a fibrous interface predominantly composed of type I collagen. Transplanted native cartilage grafts remain as inert structures within cartilage defects and fail to induce integrative cartilage repair which rather demands additional cells provided by additional bone marrow stimulation. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:???-???, 2015.
EVALuna2:15819

Locally renewing resident synovial macrophages provide a protective barrier for the joint - Culemann, Stephan; Grüneboom, Anika; Nicolás-Ávila, José Ángel; Weidner, Daniela; Lämmle, Katrin Franziska; Rothe, Tobias; Quintana, Juan A.; Kirchner, Philipp; Krljanac, Branislav; Eberhardt, Martin; Ferrazzi, Fulvia; Kretzschmar, Elke; et al. (Nature, 2019)
Macrophages are considered to contribute to chronic inflammatory diseases such as rheumatoid arthritis1. However, both the exact origin and the role of macrophages in inflammatory joint disease remain unclear. Here we use fate-mapping approaches in conjunction with three-dimensional light-sheet fluorescence microscopy and single-cell RNA sequencing to perform a comprehensive spatiotemporal analysis of the composition, origin and differentiation of subsets of macrophages within healthy and inflamed joints, and study the roles of these macrophages during arthritis. We find that dynamic membrane-like structures, consisting of a distinct population of CX3CR1+ tissue-resident macrophages, form an internal immunological barrier at the synovial lining and physically seclude the joint. These barrier-forming macrophages display features that are otherwise typical of epithelial cells, and maintain their numbers through a pool of locally proliferating CX3CR1− mononuclear cells that are embedded into the synovial tissue. Unlike recruited monocyte-derived macrophages, which actively contribute to joint inflammation, these epithelial-like CX3CR1+ lining macrophages restrict the inflammatory reaction by providing a tight-junction-mediated shield for intra-articular structures. Our data reveal an unexpected functional diversification among synovial macrophages and have important implications for the general role of macrophages in health and disease.
CRIS-Team Scopus Importer:2019-08-16

Mechanical properties of hyaline and repair cartilage studied by nanoindentation - Franke, Oliver; Durst, Karsten; Maier, Verena; Göken, Mathias; Birkholz, Torsten; Schneider, Holm; Hennig, Friedrich; Gelse, Kolja (Acta Biomaterialia, 2007)
Articular cartilage is a highly organized tissue that is well adapted to the functional demands in joints but difficult to replicate via tissue engineering or regeneration. Its viscoelastic properties allow cartilage to adapt to both slow and rapid mechanical loading. Several cartilage repair strategies that aim to restore tissue and protect it from further degeneration have been introduced. The key to their success is the quality of the newly formed tissue. In this study, periosteal cells loaded on a scaffold were used to repair large partial-thickness cartilage defects in the knee joint of miniature pigs. The repair cartilage was analyzed 26 weeks after surgery and compared both morphologically and mechanically with healthy hyaline cartilage. Contact stiffness, reduced modulus and hardness as key mechanical properties were examined in vitro by nanoindentation in phosphate-buffered saline at room temperature. In addition, the influence of tissue fixation with paraformaldehyde on the biomechanical properties was investigated. Although the repair process resulted in the formation of a stable fibrocartilaginous tissue, its contact stiffness was lower than that of hyaline cartilage by a factor of 10. Fixation with paraformaldehyde significantly increased the stiffness of cartilaginous tissue by one order of magnitude, and therefore, should not be used when studying biomechanical properties of cartilage. Our study suggests a sensitive method for measuring the contact stiffness of articular cartilage and demonstrates the importance of mechanical analysis for proper evaluation of the success of cartilage repair strategies.
Created from Fastlane, Scopus look-up
Keywords: Cartilage; Nanoindentation; Soft tissues; Stiffness; Storage effect

miR-148a promotes plasma cell differentiation and targets the germinal center transcription factors Mitf and Bach2 - Porstner, Martina; Winkelmann, Rebecca; Daum, Patrick; Schmid, Julia; Pracht, Katharina; Corte-Real, Joana; Schreiber, Sandra; Haftmann, Claudia; Brandl, Andreas; Mashreghi, Mir-Farzin; Gelse, Kolja; Hauke, Manuela; et al. (European Journal of Immunology, 2015)
B cells undergo affinity maturation and class switch recombination of their immunoglobulin receptors during a germinal center (GC) reaction, before they differentiate into long-lived antibody-secreting plasma cells (PCs). Transcription factors such as Bach2 and Mitf are essential during this process, as they delay premature differentiation of GC B cells by repressing Blimp-1 and IRF4, two transcription factors required for terminal PC differentiation. Therefore, Bach2 and Mitf expression must be attenuated in activated B cells to allow terminal PC differentiation, but the precise mechanism remains enigmatic. Here, we provide evidence that miR-148a, a small noncoding microRNA, fosters PC differentiation and survival. Next-generation sequencing revealed that miR-148a is the most abundant microRNA in primary human and murine PCs, and its expression is upregulated in activated murine B cells and coincides with Blimp-1 synthesis. miR-148a targets Bach2, Mitf and proapoptotic factors such as PTEN and Bim. When prematurely expressed, miR-148a promotes the differentiation and survival of plasmablasts and reduces frequencies of IgG1(+) cells in primary B-cell cultures. In summary, we propose that miR-148a is a new player in the regulatory network controlling terminal PC differentiation and could, therefore, be a therapeutic target for interfering with PC differentiation and survival.
EVALuna2:13632

Modular lattice constructs for biological joint resurfacing - Gelse, Kolja; Biggemann, Jonas; Stumpf, Martin; Halmheu, Melissa; Grüneboom, Anika; Scholtysek, Carina; Pachowsky, Milena; Kleyer, Arnd; Hueber, Axel; Krönke, Gerhard; Fey, Tobias (Tissue Engineering: Parts A, B, and C, 2019)
Problem: The generation of tissue-engineered cartilage constructs has made great progress over the last decades, however, the fixation of the grafts to the subchondral bone plate is still an unresolved problem. The aim of this study was to investigate a modular lattice concept as an anchoring basis for biological joint resurfacing that is stably fixed to subchondral bone, versatile for any surface shape, and permissive for cellular repopulation. Methods: Ceramic building blocks (hydroxyapatite, β-tricalcium phosphate, biphasic calcium phosphate, alumina and bioactive glass) including anchoring pins were fabricated by transfer injection molding technique. The cellular repopulation of the building blocks and cellular differentiation of human mesenchymal stem cells (hBMSC) was analysed under the influence of platelet-rich plasma, transforming growth factor-β and bone morphogenetic protein-2. A lattice construct of anchoring pins fixed to subchondral bone specimen and interposed hBMSC within collagen-hydrogel were cultured under dynamic conditions in spinner flasks for 4 weeks. The 3D constructs were analyzed by high-resolution micro computertomography (µCT), light-sheet fluorescence microscopy and histology. Pin fixation was analysed by pull-out tests. Results: Building Block-modules of complex shape with anchoring pins can be individually arranged to the subchondral bone by simple press-fit principle. Pull-out tensile stress exceeded 6 MPa. Human BMSCs required stimulation by TGF-β or BMP-2 to undergo chondrogenic differentiation. Dynamic culturinges of 3-dimensional explant constructscultures demonstrated the stability of the modular lattice construct and the interposed cell-loaded hydrogel remained within the lattice elements. hBMSCs within the collagen hydrogel underwent chondrogenic differentiation and formed a matrix that merged with the lattice structure of building blocks. Conclusions: The current work presents a proof-of-principle concept for a lattice structure that provides the stable mechanical bonding and biological milieu for the bone-cartilage interface. The anchoring elements represent an integral part of the lattice structure and provide the basis for future biological joint resurfacing by multilayer constructs. <br

„Natural Running“: Biomechanischer Vergleich von Vorfuß- oder Rückfußlauf - Gelse, Kolja; Knorz, Sebastian; Kluge, Felix; Hotfiel, Thilo; Eskofier, Björn; Krinner, Sebastian (Sports Orthopaedics and Traumatology, 2017)

Natural Running: Biomechanischer Vergleich von Vorfuß- und Rückfußlauf - Knorz, Sebastian; Krinner, Sebastian; Kluge, Felix; Lochmann, Matthias; Hennig, Friedrich; Gelse, Kolja (German Congress of Orthopaedics and Traumatology (DKOU 2016), 2016)

Nintedanib inhibits fibroblast activation and ameliorates fibrosis in preclinical models of systemic sclerosis - Huang, Jingang; Beyer, Christian; Palumbo-Zerr, Katrin; Zhang, Yun; Distler, Alfiya; Gelse, Kolja; Distler, Oliver; Schett, Georg; Wollin, Lutz; Distler, Jörg; Ramming, Andreas (Annals of the Rheumatic Diseases, 2015)
Nintedanib is a tyrosine kinase inhibitor that has recently been shown to slow disease progression in idiopathic pulmonary fibrosis in two replicate phase III clinical trials. The aim of this study was to analyse the antifibrotic effects of nintedanib in preclinical models of systemic sclerosis (SSc) and to provide a scientific background for clinical trials in SSc.The effects of nintedanib on migration, proliferation, myofibroblast differentiation and release of extracellular matrix of dermal fibroblasts were analysed by microtitre tetrazolium and scratch assays, stress fibre staining, qPCR and SirCol assays. The antifibrotic effects of nintedanib were evaluated in bleomycin-induced skin fibrosis, in a murine sclerodermatous chronic graft-versus-host disease model and in tight-skin-1 mice.Nintedanib dose-dependently reduced platelet-derived growth factor-induced and transforming growth factor-?-induced proliferation and migration as well as myofibroblast differentiation and collagen release of dermal fibroblasts from patients with and healthy individuals. Nintedanib also inhibited the endogenous activation of SSc fibroblasts. Nintedanib prevented bleomycin-induced skin fibrosis in a dose-dependent manner and was also effective in the treatment of established fibrosis. Moreover, treatment with nintedanib ameliorated fibrosis in the chronic graft-versus-host disease model and in tight-skin-1 mice in well-tolerated doses.We demonstrate that nintedanib effectively inhibits the endogenous as well as cytokine-induced activation of SSc fibroblasts and exerts potent antifibrotic effects in different complementary mouse models of SSc. These data have direct translational implications for clinical trials with nintedanib in SSc.
EVALuna2:13086

Osteosynthesis or arthroplasty of fractures near the knee joint in geriatric patients – a clinical-economical comparison - Pasurka, Mario; Krinner, Sebastian; Gelse, Kolja (Zeitschrift für Orthopädie und Unfallchirurgie, 2020)
BACKGROUND: The treatment of fractures of the tibial plateau or distal femur often represents a severe problem in geriatric patients. In particular, complex fracture types and concomitant severe osteoporosis are confronted with inferior results following internal fixation. Therefore, primary arthroplasty is increasingly propagated for such particular cases. PATIENTS, MATERIALS AND METHODS: In 16 patients suffering from fractures of the distal femur or tibial plateau were treated either by internal fixation (n = 8) or primary arthroplasty (n = 8). The outcome of each case was retrospectively analysed according to clinical and economic criteria. RESULTS: In the investigated geriatric patients, primary arthroplasty was significantly superior to internal fixation regarding mobilisation and range of motion without being inferior in cost-effectiveness. CONCLUSION: Compared to internal fixation, primary arthroplasty represents an efficient and cost-effective therapeutical option for the treatment of complex fractures of the distal femur or tibial plateau of the elderly patient.
CRIS-Team Scopus Importer:2020-06-30

Patellofemoral dysbalance and genua valga: outcome after femoral varisation osteotomies - Dickschas, Joerg; Ferner, Felix; Lutter, Christoph; Gelse, Kolja; Harrer, Joerg; Strecker, Wolf (Archives of Orthopaedic and Trauma Surgery, 2018)
Patellofemoral dysbalance may be caused by trochlear dysplasia, an elevated TTTG distance, femoral or tibial torsional deformities, patella alta, or a genu valgum. The surgical procedure for the treatment of a genu valgum is varisation osteotomy, usually in the femoral aspect. Several authors believe that a genu valgum is one cause of patellofemoral dysbalance, but studies about the outcome of the treatment with a varisation osteotomy are rare.Nineteen knees in 18 patients, aged on average 28 (16-52) years were investigated in a retrospective study. The patients had symptoms of patellofemoral instability or anterior knee pain due to a genu valgum, without symptoms of a lateral femorotibial compartment. All patients underwent a femoral varisation osteotomy. The diagnostic investigation prior to surgery included full-leg radiographs and torsional angle CT scans. The pre-surgery and follow-up investigation included the visual analog scale (VAS), the Kujala score, the Japanese Knee Society score, the Lysholm score.The mean duration of follow-up was 44(10-132) months. The mean preoperative mechanical valgus was 5.6° (range 4-10°). Twelve patients mentioned patellar instability as the main symptom while 14 mentioned anterior knee pain. No redislocation occurred in the follow-up period. Anterior knee pain on the VAS (p value < 0.001) was significantly reduced (5.6-2.1). The Japanese Knee Society score improved from 87 to 93 (p value 0.013) points, the Kujala score improved significantly from 72 to 87 (p value 0.009), and the Lysholm score significantly from 76 to 92 (p value < 0.001).Genua valga can lead to patellofemoral dysbalance, treatment of this condition is femoral varisation osteotomy. In this study, patellofemoral stability was achieved and anterior knee pain was significantly reduced. Significant improvements in clinical scores proved the success of the treatment.IV, case series.
EVALuna2:15868

PEDF Is Associated with the Termination of Chondrocyte Phenotype and Catabolism of Cartilage Tissue - Klinger, Patricia; Lukassen, Sören; Ferrazzi, Fulvia; Ekici, Arif Bülent; Hotfiel, Thilo; Swoboda, Bernd; Aigner, T.; Gelse, Kolja (BioMed Research International, 2017)
Objective. To investigate the expression and target genes of pigment epithelium-derived factor (PEDF) in cartilage and chondrocytes, respectively. Methods. We analyzed the expression pattern of PEDF in different human cartilaginous tissues including articular cartilage, osteophytic cartilage, and fetal epiphyseal and growth plate cartilage, by immunohistochemistry and quantitative real-time (qRT) PCR. Transcriptome analysis after stimulation of human articular chondrocytes with rhPEDF was performed by RNA sequencing (RNA-Seq) and confirmed by qRT-PCR. Results. Immunohistochemically, PEDF could be detected in transient cartilaginous tissue that is prone to undergo endochondral ossification, including epiphyseal cartilage, growth plate cartilage, and osteophytic cartilage. In contrast, PEDF was hardly detected in healthy articular cartilage and in the superficial zone of epiphyses, regions that are characterized by a permanent stable chondrocyte phenotype. RNA-Seq analysis and qRT-PCR demonstrated that rhPEDF significantly induced the expression of a number of matrix-degrading factors including SAA1, MMP1, MMP3, and MMP13. Simultaneously, a number of cartilage-specific genes including COL2A1, COL9A2, COMP, and LECT were among the most significantly downregulated genes. Conclusions. PEDF represents a marker for transient cartilage during all neonatal and postnatal developmental stages and promotes the termination of cartilage tissue by upregulation of matrix-degrading factors and downregulation of cartilage-specific genes. These data provide the basis for novel strategies to stabilize the phenotype of articular cartilage and prevent its degradation.
EVALuna2:9364

Poly(ADP-ribose) polymerase-1 regulates fibroblast activation in systemic sclerosis - Zhang, Yun; Pötter, Sebastian; Chen, Chih-Wei; Liang, Ruifang; Gelse, Kolja; Ludolph, Ingo; Horch, Raymund E.; Distler, Oliver; Schett, Georg; Distler, Jörg; Dees, Clara (Annals of the Rheumatic Diseases, 2018)
OBJECTIVES: The enzyme poly(ADP-ribose) polymerase-1 (PARP-1) transfers negatively charged ADP-ribose units to target proteins. This modification can have pronounced regulatory effects on target proteins. Recent studies showed that PARP-1 can poly(ADP-ribosyl)ate (PARylate) Smad proteins. However, the role of PARP-1 in the pathogenesis of systemic sclerosis (SSc) has not been investigated. METHODS: The expression of PARP-1 was determined by quantitative PCR and immunohistochemistry. DNA methylation was analysed by methylated DNA immunoprecipitation assays. Transforming growth factor-β (TGFβ) signalling was assessed using reporter assays, chromatin immunoprecipitation assays and target gene analysis. The effect of PARP-1 inactivation was investigated in bleomycin-induced and topoisomerase-induced fibrosis as well as in tight-skin-1 (Tsk-1) mice. RESULTS: The expression of PARP-1 was decreased in patients with SSc, particularly in fibroblasts. The promoter of PARP-1 was hypermethylated in SSc fibroblasts and in TGFβ-stimulated normal fibroblasts. Inhibition of DNA methyltransferases (DNMTs) reduced the promoter methylation and reactivated the expression of PARP-1. Inactivation of PARP-1 promoted accumulation of phosphorylated Smad3, enhanced Smad-dependent transcription and upregulated the expression of TGFβ/Smad target genes. Inhibition of PARP-1 enhanced the effect of TGFβ on collagen release and myofibroblast differentiation in vitro and exacerbated experimental fibrosis in vivo. PARP-1 deficiency induced a more severe fibrotic response to bleomycin with increased dermal thickening, hydroxyproline content and myofibroblast counts. Inhibition of PARylation also exacerbated fibrosis in Tsk-1 mice and in mice with topoisomerase-induced fibrosis. CONCLUSION: PARP-1 negatively regulates canonical TGFβ signalling in experimental skin fibrosis. The downregulation of PARP-1 in SSc fibroblasts may thus directly contribute to hyperactive TGFβ signalling and to persistent fibroblast activation in SSc.
EVALuna2:34150

Pre-operative sensor-based gait parameters predict functional outcome after total knee arthroplasty - Kluge, Felix; Hannink, Julius; Pasluosta, C. F.; Klucken, Jochen; Gaßner, Heiko; Gelse, Kolja; Eskofier, Björn; Krinner, Sebastian (Gait & Posture, 2018)

Production and Secretion of Gelsolin by Both Human Macrophage- and Fibroblast-like Synoviocytes and GSN Modulation in the Synovial Fluid of Patients with Various Forms of Arthritis - Feldt, Jessica; Schicht, Martin; Welss, Jessica; Gelse, Kolja; Sesselmann, Stefan; Tsokos, Michael; Socher, Eileen; Garreis, Fabian; Mueller, Thomas; Paulsen, Friedrich (Biomedicines, 2022)
Gelsolin (GSN) is an actin-binding protein involved in cell formation, metabolism and wound closure processes. Since this protein is known to play a role in arthritis, here we investigate how the synovial membrane with its specific synoviocytes contributes to the expression of GSN and how the amount of GSN expressed is modulated by different types of arthritis. Synovial membranes from adult healthy subjects and patients with rheumatoid arthritis (RA) and osteoarthritis (OA) are analyzed by immunofluorescence, Western blot and ELISA. Macrophage-like synoviocytes (MLS) and fibroblast-like synoviocytes (FLS) were isolated, cultured and analyzed for their potential to produce and secrete GSN. In addition, the GSN concentrations in the synovial fluid of various forms of arthritis are determined by ELISA. GSN is produced by the healthy and arthritic synovial membranes. Both forms of synoviocytes (MLS and FLS) release GSN. The results show that there is a significant reduction in GSN in the synovial fluid in adult patients with OA. This reduction is also detectable in adult patients with RA but is not as evident. In juvenile arthritis, there is a slight increase in GSN concentration in the synovial fluid. This study shows that primary MLS and FLS express GSN and that these cells, in addition to articular chondrocytes, contribute to GSN levels in synovial fluid. Furthermore, GSN concentrations are modulated in different types of arthritis. Further studies are needed to fully understand how GSN is involved in joint homeostasis.<br
Keywords: arthritis; gelsolin; synovial fluid; synoviocytes

PU.1 controls fibroblast polarization and tissue fibrosis - Wohlfahrt, Thomas; Rauber, Simon; Uebe, Steffen; Luber, Markus; Soare, Alina; Ekici, Arif Bülent; Weber, Stefanie; Matei, Alexandru-Emil; Chen, Chih-Wei; Maier, Christiane; Karouzakis, Emmanuel; Kiener, Hans P.; et al. (Nature, 2019)
Fibroblasts are polymorphic cells with pleiotropic roles in organ morphogenesis, tissue homeostasis and immune responses. In fibrotic diseases, fibroblasts synthesize abundant amounts of extracellular matrix, which induces scarring and organ failure. By contrast, a hallmark feature of fibroblasts in arthritis is degradation of the extracellular matrix because of the release of metalloproteinases and degrading enzymes, and subsequent tissue destruction. The mechanisms that drive these functionally opposing pro-fibrotic and pro-inflammatory phenotypes of fibroblasts remain unknown. Here we identify the transcription factor PU.1 as an essential regulator of the pro-fibrotic gene expression program. The interplay between transcriptional and post-transcriptional mechanisms that normally control the expression of PU.1 expression is perturbed in various fibrotic diseases, resulting in the upregulation of PU.1, induction of fibrosis-associated gene sets and a phenotypic switch in extracellular matrix-producing pro-fibrotic fibroblasts. By contrast, pharmacological and genetic inactivation of PU.1 disrupts the fibrotic network and enables reprogramming of fibrotic fibroblasts into resting fibroblasts, leading to regression of fibrosis in several organs.
EVALuna2:35476

Recombinant human gelsolin promotes the migration of human articular cartilage chondrocytes by regulating gene expression in vitro. - Feldt, Jessica; Welss, Jessica; Schropp, Verena; Gelse, Kolja; Tsokos, Michael; Paulsen, Friedrich (Osteoarthritis and Cartilage Open, 2020)
OBJECTIVE: It is known that recombinant human gelsolin (rhuGSN) supports wound closure and migration processes in avascular tissue. Since articular cartilage degradation plays an important role in osteoarthritis (OA), we are investigating how rhuGSN affects regeneration processes in human articular cartilage and represents a promising new therapeutic approach for the treatment of OA. METHODS: Primary human chondrocytes (phCs) from articular knee cartilage were cultured with different concentrations of rhuGSN to analyse its direct effect in vitro. In addition, phCs were stimulated with 10 ng/mL IL-1β or TNF-α to simulate osteoarthritis in vitro and treated with different concentrations of rhuGSN to investigate the beneficial effect in disease treatment. Cytokine secretion and gene expression as well as wound assays were performed. RESULTS: GSN significantly promotes wound closure in phCs after 60 h compared to untreated cells. After 24 h treatment with 30 μg/mL rhuGSN, TGF-β secretion increases significantly in the in vitro osteoarthritis model. Gene expression of MMP1 as well as SPARC is reduced in chondrocytes due to treatment with GSN in the OA model. At the same time, CXCR4 expression increases significantly after 24 h treatment with 3 μg/mL GSN. CONCLUSION: In the in vitro model of osteoarthritis, rhuGSN promotes wound closure of chondrocytes by a supported migration as well as expression of reconstructive and down regulated expression of deconstructive genes concentration dependently. Further experiments are needed to fully understand the beneficial effect of gelsolin on human chondrocytes and to verify this promising approach for a pharmacological treatment of osteoarthritis.
EVALuna2:515804

SIGNATURE OF CIRCULATING MICRORNAS IN OSTEOARTHRITIS - Beyer, Christian; Zampetaki, A.; Lin, N. -Y.; Kleyer, Arnd; Perricone, C.; Iagnocco, A. M.; Distler, A.; Langley, S. L.; Gelse, Kolja; Sesselmann, Stefan; Lorenzini, R.; Niemeier, A.; et al. (2014)
EVALuna2:34462

Signature of circulating microRNAs in osteoarthritis - Beyer, Christian; Zampetaki, Anna; Lin, Neng-Yu; Kleyer, Arnd; Perricone, Carlo; Iagnocco, Annamaria; Distler, Alfiya; Langley, Sarah R.; Gelse, Kolja; Sesselmann, Stefan; Lorenzini, Rolando; Niemeier, Andreas; et al. (Annals of the Rheumatic Diseases, 2015)
Osteoarthritis is the most common form of arthritis and a major socioeconomic burden. Our study is the first to explore the association between serum microRNA levels and the development of severe osteoarthritis of the knee and hip joint in the general population.We followed 816 Caucasian individuals from 1995 to 2010 and assessed joint arthroplasty as a definitive outcome of severe osteoarthritis of the knee and hip. After a microarray screen, we validated 12 microRNAs by real-time PCR in the entire cohort at baseline.In Cox regression analysis, three microRNAs were associated with severe knee and hip osteoarthritis. let-7e was a negative predictor for total joint arthroplasty with an adjusted HR of 0.75 (95% CI 0.58 to 0.96; p=0.021) when normalised to U6, and 0.76 (95% CI 0.6 to 0.97; p=0.026) after normalisation to the Ct average. miRNA-454 was inversely correlated with severe knee or hip osteoarthritis with an adjusted HR of 0.77 (95% CI 0.61 to 0.97; p=0.028) when normalised to U6. This correlation was lost when data were normalised to Ct average (p=0.118). Finally, miRNA-885-5p showed a trend towards a positive relationship with arthroplasty when normalised to U6 (HR 1.24; 95% CI 0.95 to 1.62; p=0.107) or to Ct average (HR 1.30; 95% CI 0.99 to 1.70; p=0.056).Our study is the first to identify differentially expressed circulating microRNAs in osteoarthritis patients necessitating arthroplasty in a large, population-based cohort. Among these microRNAs, let-7e emerged as potential predictor for severe knee or hip osteoarthritis.
EVALuna2:10852

Stellenwert des Débridements bei der Behandlung fokaler (Grad II – III) Knorpelschäden des Kniegelenks. Systematische Literaturübersicht und Empfehlungen der AG Geweberegeneration (DGOU) - Gelse, Kolja; Angele, Peter; Behrens, Peter; Brucker, Peter U.; Fay, Jakob; Guenther, Daniel; Kreuz, Peter; Luetzner, Joerg; Madry, Henning; Mueller, Peter E.; Niemeyer, Philipp; Pagenstert, Geert; et al. (Zeitschrift für Orthopädie und Unfallchirurgie, 2018)
In clinical practice, there is still no definite treatment algorithm for focal, partial thickness cartilage lesions (grade II - III). It is well-established that debridement (shaving/lavage) of large degenerative cartilage lesions is not recommended, but there is no such recommendation in the case of focal, partial thickness cartilage defects.The scientific rationale of cartilage shaving and joint lavage was investigated and a systematic analysis was performed of the literature on the clinical effect of cartilage debridement. Furthermore, a consensus statement on this issue was developed by the working group on Clinical Tissue Regeneration of the German Society of Orthopaedics and Trauma (DGOU).The therapeutic approach is different for asymptomatic lesions with biomechanical stable residual cartilage tissue and clinically symptomatic defects with unstable fragments. The benefit of a joint lavage or surface smoothening of focal partial thickness has not been proved. Even more importantly, the mechanical or thermal resection of cartilage tissue even induces a zone of necrosis in adjacent cartilage, and thus leads to additional injury. Therefore, large scale smoothening (shaving) of clinically asymptomatic, fibrillated or irregular cartilage defects should not be performed. However, if there are clinical symptoms, resection of unstable and delaminated cartilage fragments may be reasonable, as it can reduce harmful shear tension in residual tissue. This can help to brake the progression of the damage and avoid formation of free bodies.The decision criteria for debridement of partial thickness focal cartilage lesions are multifactorial and include the clinical symptoms, the size and the degree of the defect, the stability of remaining cartilage, localisation of the defect, and individual patient-specific parameters. Debridement is not recommended for asymptomatic lesions, but may be reasonable for symptomatic cases with unstable tissue.
EVALuna2:104968

TGF-β-induced epigenetic deregulation of SOCS3 facilitates STAT3 signaling to promote fibrosis - Dees, Clara; Pötter, Sebastian; Zhang, Yun; Bergmann, Christina; Zhou, Xiang; Luber, Markus; Wohlfahrt, Thomas; Karouzakis, Emmanuel; Ramming, Andreas; Gelse, Kolja; Yoshimura, Akihiko; Jaenisch, Rudolf; et al. (Journal of Clinical Investigation, 2020)
Fibroblasts are key effector cells in tissue remodeling. They remain persistently activated in fibrotic diseases, resulting in progressive deposition of extracellular matrix. Although fibroblast activation may be initiated by external factors, prolonged activation can induce an “autonomous,” self-maintaining profibrotic phenotype in fibroblasts. Accumulating evidence suggests that epigenetic alterations play a central role in establishing this persistently activated pathologic phenotype of fibroblasts. We demonstrated that in fibrotic skin of patients with systemic sclerosis (SSc), a prototypical idiopathic fibrotic disease, TGF-β induced the expression of DNA methyltransferase 3A (DNMT3A) and DNMT1 in fibroblasts in a SMAD-dependent manner to silence the expression of suppressor of cytokine signaling 3 (SOCS3) by promoter hypermethylation. Downregulation of SOCS3 facilitated activation of STAT3 to promote fibroblast-to-myofibroblast transition, collagen release, and fibrosis in vitro and in vivo. Reestablishment of the epigenetic control of STAT3 signaling by genetic or pharmacological inactivation of DNMT3A reversed the activated phenotype of SSc fibroblasts in tissue culture, inhibited TGF-β-dependent fibroblast activation, and ameliorated experimental fibrosis in murine models. These findings identify a pathway of epigenetic imprinting of fibroblasts in fibrotic disease with translational implications for the development of targeted therapies in fibrotic diseases.
CRIS-Team Scopus Importer:2020-05-12

The tyrosine phosphatase SHP2 controls TGFβ-induced STAT3 signaling to regulate fibroblast activation and fibrosis - Zehender, Ariella; Huang, Jingang; Gyoerfi, Andrea-Hermina; Matei, Alexandru-Emil; Thuong Trinh-Minh,; Xu, Xiaohan; Li, Yi-Nan; Chen, Chih-Wei; Lin, Jianping; Dees, Clara; Beyer, Christian; Gelse, Kolja; et al. (Nature Communications, 2018)
Uncontrolled activation of TGFβ signaling is a common denominator of fibrotic tissue remodeling. Here we characterize the tyrosine phosphatase SHP2 as a molecular checkpoint for TGFβ-induced JAK2/STAT3 signaling and as a potential target for the treatment of fibrosis. TGFβ stimulates the phosphatase activity of SHP2, although this effect is in part counterbalanced by inhibitory effects on SHP2 expression. Stimulation with TGFβ promotes recruitment of SHP2 to JAK2 in fibroblasts with subsequent dephosphorylation of JAK2 at Y570 and activation of STAT3. The effects of SHP2 on STAT3 activation translate into major regulatory effects of SHP2 on fibroblast activation and tissue fibrosis. Genetic or pharmacologic inactivation of SHP2 promotes accumulation of JAK2 phosphorylated at Y570, reduces JAK2/STAT3 signaling, inhibits TGFβ-induced fibroblast activation and ameliorates dermal and pulmonary fibrosis. Given the availability of potent SHP2 inhibitors, SHP2 might thus be a potential target for the treatment of fibrosis.
EVALuna2:34477

Three-Dimensional Biomechanical Analysis of Rearfoot and Forefoot Running - Knorz, Sebastian; Kluge, Felix; Gelse, Kolja; Schulz-Drost, Stefan; Hotfiel, Thilo; Lochmann, Matthias; Eskofier, Björn; Krinner, Sebastian (Orthopaedic Journal of Sports Medicine, 2017)

Transplantation of Chemically Processed Decellularized Meniscal Allografts: A Pilot Sheep Study - Gelse, Kolja; Körber, Ludwig; Schöne, Martin; Raum, Kay; Koch, Peter; Pachowsky, Milena; Welsch, Götz; Breiter, Roman (Cartilage, 2017)
Objective The aim of this study was to evaluate the chondroprotective effect of chemically decellularized meniscal allografts transplanted into the knee joints of adult merino sheep. Methods Lateral sheep meniscal allografts were chemically processed by a multistep method to yield acellular, sterile grafts. The grafts were transplanted into the knee joints of sheep that were treated by lateral meniscectomy. Joints treated by meniscectomy only and untreated joints served as controls. The joints were analyzed morphologically 6 and 26 weeks after surgery by the macroscopical and histological OARSI (Osteoarthritis Research Society International) score. Additionally, the meniscal grafts were biomechanically tested by cyclic indentation. Results Lateral meniscectomy was associated with significant degenerative changes of the articular cartilage of the lateral joint compartment. Transplanted lateral meniscal allografts retained their integrity during the observation period without inducing significant synovitis or foreign body reactions. Cellular repopulation of the grafts was only present on the surface and the periphery of the lateral meniscus, but was still completely lacking in the center of the grafts at week 26. Transplantation of processed meniscal allografts could not prevent degenerative changes of the articular cartilage in the lateral joint compartment. Compared with healthy menisci, the processed grafts were characterized by a significantly reduced dynamic modulus, which did not improve during the observation period of 26 weeks in vivo. Conclusion Chemically decellularized meniscal allografts proved their biocompatibility and durability without inducing immunogenic reactions. However, insufficient recellularization and inferior stiffness of the grafts hampered chondroprotective effects on the articular cartilag

Trefoil factor 3 (TFF3) is involved in cell migration for skeletal repair - Krüger, Katharina; Schmidt, Sebastian; Paulsen, Friedrich; Ignatius, Anita; Klinger, Patricia; Hotfiel, Thilo; Swoboda, Bernd; Gelse, Kolja (International Journal of Molecular Sciences, 2019)
The aim of the study was to explore the possible role of Trefoil Factor Family peptide 3 (TFF3) for skeletal repair. The expression of TFF3 was analyzed in human joint tissues as well as in a murine bone fracture model. Serum levels of TFF3 following a defined skeletal trauma in humans were determined by ELISA. The mRNA expression of TFF3 was analyzed under normoxia and hypoxia. Expression analysis after stimulation of human mesenchymal progenitor cells (MPCs) with TFF3 was performed by RT2 Profiler PCR Array. The effect of recombinant human (rh)TFF3 on MPCs was analysed by different migration and chemotaxis assays. The effect on cell motility was also visualized by fluorescence staining of F-Actin. TFF3 was absent in human articular cartilage, but strongly expressed in the subchondral bone and periosteum of adult joints. Strong TFF3 immunoreactivity was also detected in murine fracture callus. Serum levels of TFF3 were significantly increased after skeletal trauma in humans. Expression analysis demonstrated that rhTFF3 significantly decreased mRNA of ROCK1. Wound healing assays showed increased cell migration of MPCs by rhTFF3. The F-Actin cytoskeleton was markedly influenced by rhTFF3. Cell proliferation was not increased by rhTFF3. The data demonstrate elevated expression of TFF3 after skeletal trauma. The stimulatory effects on cell motility and migration of MPCs suggest a role of TFF3 in skeletal repair.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Cell migration; Chemotaxis; Fracture healing; Mesenchymal progenitor cells; TFF3

Type 2 innate lymphoid cell counts are increased in patients with systemic sclerosis and correlate with the extent of fibrosis - Wohlfahrt, Thomas; Usherenko, Svetlana; Englbrecht, Matthias; Dees, Clara; Weber, Stefanie; Beyer, Christian; Gelse, Kolja; Distler, Oliver; Schett, Georg; Distler, Jörg; Ramming, Andreas (Annals of the Rheumatic Diseases, 2016)
Objective Type 2 innate lymphoid cells (ILC2s), a recently identified population of lymphoid cells lacking lineage-specific receptors, promote type 2 immunity and tissue remodelling. However, the contributive role of ILC2s in the pathogenesis of systemic sclerosis (SSc) is unknown. We aimed to evaluate the levels and correlations with fibrotic manifestations in SSc. Methods 69 patients with SSc and 47 healthy controls were included. Blood samples and skin sections were analysed by flow cytometry and immunohistochemically by staining two complementary panels of markers. Results Dermal and circulating ILC2s were significantly elevated in patients with SSc compared with controls. Dermal, but not circulating ILC2s were activated. Stratification of the SSc population in patients with limited cutaneous SSc (lcSSc) and diffuse cutaneous SSc (dcSSc) demonstrated increased levels of ILC2s in both subgroups with significantly higher frequencies in dcSSc compared with lcSSc. Moreover, dermal and circulating ILC2 counts correlated closely with the modified Rodnan skin score and with the presence of pulmonary fibrosis. Conclusions ILC2 counts are elevated in patients with SSc and correlate with the extent of skin fibrosis and the presence of interstitial lung disease providing compelling evidence for profibrotic effect of ILC2s in SSc.
EVALuna2:13149